Beneficial Oral Biofilms as Smart Bioactive Interfaces - Gutt, Beatrice; Ren, Qun; Hauser-Gerspach, Irmgard; Kardas, Piotr; Stübinger, Stefan; Astasov-Frauenhoffer, Monika; Waltimo, Tuomas (Frontiers in Microbiology, 2018)
Periodontitis is a very common health problem caused by formation of pathogenic bacterial biofilm that triggers inflammation resulting in either reversible gingivitis or irreversible periodontal hard and soft tissue damages, leading to loss of teeth when left untreated. Commensal bacteria play an important role in oral health in many aspects. Mainly by colonizing oral tissues, they (i) contribute to maturation of immune response, and (ii) foreclose attachment of pathobiont and, therefore, prevent from infection. The main goal of the study was to investigate if blocking of receptors on a commensal biofilm can prevent or reduce the attachment of pathogenic strains. To do so, biofilm produced by commensal Streptococcus sanguinis was treated with whole cell lysate of pathobionts Fusobacterium nucleatum or Porphyromonas gingivalis, followed by incubation with respective strain(s). The study revealed significant reduction in pathobiont adhesion to lysate-treated commensal biofilm. Therefore, adhesion of pathobionts onto the lysate-blocked biofilm was hindered; however, not completely eliminated supporting the idea that such approach in the oral cavity would benefit the production of a well-balanced and healthy bioactive interface.